Adolescent pregnancy & parenting [videorecording] : moving beyond stereotypes - HSTN (Carrollton : HSTN, 1998)
This program details the medical, psychosocial, and educational needs of pregnant and parenting teens, and presents an analysis of the social issues that influence adolescent decision making regarding sexuality. It also highlights prevention strategies that advocate delayed sexual involvement and raise awareness regarding adolescent pregnancy and STDs
201-0305
Keywords: Pregnancy; Obstetrical Nursing; Parenting